The influence of job content and autonomy on psychological well-being through work identity and job crafting among pharmacists in Pakistan - Rana Muhammad Zahid Mushtaq; Naeem Rasool; Zaka Ur Rehman; Usama Bin Naeem; Muhammad Azeem; Tehreem Fayyaz; Mehmood Ahmad; Waqas Ahmad (PLoS ONE, 2026)
Background Psychological well-being of pharmacists is necessary for safe and effective healthcare delivery, particularly in high-stress environments. The present study was aimed to investigate the influence of job content on psychological well-being among the registered pharmacists in Pakistan along with the mediating roles of work identity and job crafting. Methods Data were collected from 564 licensed pharmacists on standardized instruments for psychological well-being (Ryff’s PWB Scale), job content (Karasek’s JCQ), work identity, and job crafting behaviors. Structural equation modeling using RStudio tested the direct, indirect, and serial mediation effects, with bootstrapped 95% confidence intervals. Results Confirmatory factor analysis indicated acceptable model reliability (e.g., Job Crafting α = 0.94, CR = 0.96; PWB α = 0.66, CR = 0.85). Bivariate correlations showed that psychological well-being was moderately associated with job crafting (r = 0.49, p < 0.01) and strongly with work identity (r = 0.57, p < 0.01). SEM analysis showed that Job content had no significant direct effect on well-being (β = −0.0362, p = 0.56), two significant indirect effects were observed: via work identity (β = 0.1397, p < 0.05) and job crafting (β = 0.1295, p < 0.05). The sequential pathway; Job content → work identity → job crafting → psychological well-being also yielded a smaller but significant effect (β = 0.0278, p < 0.05). Conclusion Our findings suggest that work identity and job crafting may mediate the relationship between job content and psychological well-being; however, these results should be interpreted cautiously given the model fit limitations.